Policing the deinstitutionalized mentally ill: toward an understanding of its function - Wachholz, Sandra (Crime, law and social change, 1993)
Although the police have long been recognized as a community health resource in the United States, this role has expanded significantly over the past several decades as a result of the deinstitutionalization movement. From a critical perspective, this article provides an analysis of the relationship between this enlarged police role and the current American socio-political order, in general, and the welfare state in particular. It is argued that in the course of handling the mentally ill the police carry out a number of functions for both the welfare state and the socio-political order, and in doing so, shore-up the social conditions which have inhibited the development of a positive, long-term care policy for the mentally ill. This article discusses three such functions and identifies an alternative social arrangement; one in which the police would not have to serve as a support for liberal-capitalism and its attendant inadequate welfare state.